An Econometric Analysis of a Production Function for New Zealand - Kam Leong Szeto (New Zealand Government, The Treasury, 2001)
Using the capital stock series recently released by Statistics New Zealand, two approaches have been employed to estimate a production function. The first approach is based on the estimation of a constant elasticity of substitution (CES) production function with a value added form. The second approach is based on a nested CES function. Using the nested structure, we allow imports as an intermediate input in the production block. The estimated results reveal that the data rejects the Cobb-Douglas specification and the use of the value added form is not justifiable.
Keywords: C51; E23; 330; CES production function; Cobb-Douglas specification